Improving Hospital Patient Falls. (May 2015) - Aydin, Carolyn; Donaldson, Nancy; Aronow, Harriet Udin; Fridman, Moshe; Brown, Diane Storer
<x xml:space="preserve">Abstract</x> OBJECTIVE: Predictive models for falls, injury falls, and restraint prevalence were explored within nursing unit structures and processes of care. BACKGROUND: The patient care team is responsible for patient safety, and improving practice models may prevent injuries and improve patient safety. METHODS: Using unit-level self-reported data from 215 hospitals, falls, injury falls, and restraint prevalence were modeled with significant covariates as predictors. RESULTS: Fewer falls/injury falls were predicted by populations with fewer frail and at-risk patients, more unlicensed care hours, and prevention protocol implementation, but not staffing per se, restraint use, or RN expertise. Lower restraint use was predicted by fewer frail patients, shorter length of stay, more RN hours, more certified RNs, and implementation of fall prevention protocols. CONCLUSION: In the presence of risk, patient injuries and safety were improved by optimizing staffing skill mix and use of prevention protocols.